Health, disability and quality of life among trans people in Sweden-a web-based survey - Galit Zeluf; Cecilia Dhejne; Carolina Orre; Louise Nilunger Mannheimer; Charlotte Deogan; Jonas Höijer; Anna Ekéus Thorson (BMC, 2016)
Abstract Background Swedish research concerning the general health of trans people is scarce. Despite the diversity of the group, most Swedish research has focused on gender dysphoric people seeking medical help for their gender incongruence, or on outcomes after medical gender-confirming interventions. This paper examines self-rated health, self-reported disability and quality of life among a diverse group of trans people including trans feminine, trans masculine, and gender nonbinary people (identifying with a gender in between male of female, or identify with neither of these genders) as well as people self-identifying as transvestites. Methods Participants were self-selected anonymously to a web-based survey conducted in 2014. Univariable and multivariable regression analyses were performed. Three backward selection regression models were conducted in order to identify significant variables for the outcomes self-rated health, self-reported disability and quality of life. Results Study participants included 796 individuals, between 15 and 94 years of age who live in Sweden. Respondents represented a heterogeneous group with regards to trans experience, with the majority being gender nonbinary (44 %), followed by trans masculine (24 %), trans feminine (19 %) and transvestites (14 %). A fifth of the respondents reported poor self-rated health, 53 % reported a disability and 44 % reported quality of life scores below the median cut-off value of 6 (out of 10). Nonbinary gender identity (adjusted Odds Ratio (aOR) = 2.19; 95 % CI: 1.24, 3.84), negative health care experiences (aOR = 1.92; 95 % CI: 1.26, 2.91) and not accessing legal gender recognition (aOR = 3.06; 95 % CI: 1.64, 5.72) were significant predictors for self-rated health. Being gender nonbinary (aOR = 2.18; 95 % CI: 1.35, 3.54) and history of negative health care experiences (aOR = 2.33; 95 % CI: 1.54, 3.52) were, in addition, associated with self-reported disability. Lastly, not accessing legal gender recognition (aOR = 0.32; 95 % CI: 0.17, 0.61) and history of negative health care experiences (aOR = 0.56; 95 % CI: 0.36, 0.88) were associated with lower quality of life. Conclusions The results of this study demonstrate that the general health of trans respondents is related to vulnerabilities that are unique for trans people in addition to other well-known health determinants.